A cross media platform for personalized leisure & entertainment: the POLYMNIA approach - Anagnostopoulos, Vasilios; Lalos, Constantinos; Chatzis, Sotirios P. (My University, 2006)
The POLYMNIA project aims to develop an intelligent cross-media platform for personalised leisure and entertainment in thematic parks or venues. The system allows the visitors to be the real protagonist in the venue. Towards this goal, POLYMNIA platform is equipped with innovative imaging technologies for real time detection, localisation and tracking of i human contenu, i.e., the human visitor within the recoding being made in real-time by the system. No constraints are imposed on the variation of the environment. New, content-based media representation and organisation schemes will be developed to provide scalable, efficient and user-oriented description of the i human contenu, enabling efficient retrieval, access, and delivery across heterogeneous media platforms. In addition, adaptive mechanisms are employed to update the system response to the current usersi information needs and preferences
Keywords: Computing & Processing (Hardware/Software); Motion pictures; Expert systems (Computer science); Content-based image retrieval